Level Of Parent Education To Knowledge About Antibiotic In Children Ages 0 – 12 Years Old In Tanjungmojo Village, Kangkung District, Kendal Regency - Elvira Rosa; Haini Santi; Anindya Tri Hardiningtyas (CV. AFDIFAL MAJU BERKAH, 2024)
Prescribing antibiotics for infectious diseases that are quite high and less wise will increase the incidence of resistance. Research objectives to determine the influence of parental education level on the knowledge of antibiotic use in children aged 0-12 years in TanjungmojoVillage, Kangkung District, Kendal Regency. The study used observational analytics with a cross sectional approach. The population in this study was all parents who had children aged 0-12 years in TanjungmojoKidul Village. The sampling technique used is purposive sampling of 55 respondents who have met the criteria of inclusion and exclusion. Education level data and further knowledge levels analyzed with Chi-Square test. Chi-Square test results between education level and knowledge level obtained p = 0.006. This shows a p value of less than 0.05 with a confidence level of 95% so there is a significant relationship between the level of education and the level of knowledge about antibiotics. There is a relationship of parents' education level to knowledge about antibiotics in children aged 0-12 years in TanjungmojoVillage Kangkung district of Kendal regency.